Study of Oxygen Vacancies on Different Facets of Anatase TiO2. Issue 9 (31st July 2019) - Wu, Yanan; Fu, Yingyi; Zhang, Li; Ren, Yuanhang; Chen, Xueying; Yue, Bin; He, Heyong
Summary of main observation and conclusion: Anatase TiO2 samples with different ratios of {101} to {001} facets were prepared with hydrothermal method and further treated under three specific calcination atmospheres (air, H2, N2 ). The characterization results indicate that {001} facets may generate more oxygen vacancies and more Ti 3+ species than {101} facets. Abstract : Oxygen vacancies are easier to form on {001} facets than on {101} facets of anatase TiO2 .